Historical pre-condition of origin and theoretical basis of the ethical doctrine of «Bhagavadgita» (Journal of Philosophy Culture and Political Science, 2018)
The relevance of the study «Bhagavad Gita» in modern society due to the fact that scientific and technological progress and the achievements of civilization in various areas of public life are accompanied by loss of moral ideals and humanistic values, which may lead to the degradation of man as an individual and spiritual being. «Bhagavadgita» asserts the priority of spirituality and the increase of ethical standards over material benefits. The article discusses the historical pre-condition and structural stages of an ethical doctrine «Bhagavadgita». In addition, the article analyzes the current relevance of the ethical teaching in the Indian literature.Key words: The Bhagavad Gita, philosophy, Kurukşhetr, yoga, world view.